Long-term physical and neurodevelopmental outcomes after antenatal betamethasone administration for congenital heart block prevention. (2nd November 2022) - Wada, Yuka Sano; Hama, Ikuko; Goto, Mikako; Ito, Yushi; Murashima, Atsuko
Abstract: Introduction: Congenital heart block (CHB) is associated with a mortality rate of 20% and requires a pacemaker in 70% of cases. Steroids can reduce morbidity and prevent the onset of CHB but may have adverse effects on growth and neurodevelopment. This study aimed to clarify the long-term effects of antenatal betamethasone administration on growth and neurodevelopment. Methods: The subjects were children with a high risk of CHB due to a high level of maternal anti-SSA/Ro antibody or a maternal history of a previous delivery of a offspring with CHB to whom antenatal betamethasone was administered. Data on body weight, height, and blood pressure were collected as physical outcomes. The Wechsler Intelligence Scale for Children (fourth edition) or the Kyoto Scale of Psychological Development and the Pervasive Developmental Disorders Autism Society Japan Rating Scale was administered to assess the neurodevelopmental outcome. Results: Fourteen children were enrolled. The body weight and height were within normal range in all children. All children had normal intelligence, and none had autism. Conclusion: Our study suggested that antenatal betamethasone administration has no negative effects on long-term physical and neurodevelopmental outcomes.